Decentering Whiteness in the Workplace: A Guide for Equity and Inclusion - Gassam Asare, Janice; Saad, Layla (Berrett-Koehler Publishers, 2023)
Your DEIJ efforts are stagnating because you continue to center whiteness. Creating a truly anti-racist organization requires learning how to identify and rectify the systemic, and often unconscious, centering of white culture and values in the workplace. Corporate America continues to struggle with racial equity in a post-George Floyd world. As the United States becomes more diverse and the public consciousness continues to shift, successful racial equity efforts in the workplace are needed now more than ever. Decentering Whiteness in the Workplace exposes the ways that white culture and expectations are centered in the modern American workplace and the fears within corporate spaces about talking candidly, openly, and honestly about whiteness, white supremacy, and anti-Blackness. Readers will discover: * A direct and straightforward analysis about what white-centering is * An evaluation of the different ways that whiteness is centered in the workplace, such as bereavement and holiday policies and dress codes * A guide on how to recognize and decenter whiteness within oneself and at work * Solutions for people to contribute individually and systemically to anti-oppression Decentering Whiteness in the Workplace provides a crucial guidebook with practical solutions for leaders, DEIJ practitioners, and anyone hoping to truly create an anti-racist workplace.